PERBANDINGAN BILL OF QUANTITY(BOQ) ANTARA METODE KONVENSIONAL DENGAN HASIL PERHITUNGAN AUTODESK REVIT (STUDI KASUS: PROYEK GEDUNG JI’RONA RS AISYIYAH BOJONEGORO) - Dony Prasetyo Budi (Jurnal Vokasi Teknik Sipil, 2025)
The construction industry is undergoing a significant transformation with the arrival of Industrial Revolution 4.0, which encourages a shift from conventional methods to more efficient and innovative technologies. Such technology is Building Information Modeling (BIM), which enables more targeted project management through automated and integrated systems. Autodesk Revit is one of the commonly used BIM software. However, the implementation of BIM in Indonesia is still not optimal, due to the limited software available and the low level of user understanding. In practice, the Bill of Quantity (BOQ) calculation is still dominated by conventional methods. Although easier to understand and cheaper, conventional methods have disadvantages such as the potential for human error and longer processing time. In contrast, BIM offers high accuracy, time efficiency, and better integration. This research aims to compare the calculation results (BOQ) between conventional and BIM methods using Autodesk Revit. The research method used is Research and Development (R&D). Later, it will go through 3 stages, namely data collection, planning, and development. From this research, it was found that the difference in BOQ calculation from the BIM method was smaller than the conventional method, with a percentage value of 8.45% in concrete volume and 7.37% in reinforcement volume. It can be concluded that the BIM method is more accurate than the conventional method.